Healthcare professionals' perceptions of patient safety for the woman in childbirth in Sweden - An interview study - Annika Skoogh; Carina Bååth; Ann‐Kristin Sandin Bojö; Marie Louise Hall‐Lord (Wiley, 2020)
Abstract Aim To describe healthcare professionals' perceptions of patient safety with a focus on the woman in connection to childbirth. Design A descriptive and qualitative design with a phenomenographic approach. Methods Individual qualitative face‐to‐face interviews with 19 healthcare professionals (midwives, nursing assistants and physicians) were conducted in three labour wards in Sweden. The data were analysed according to Dahlgren and Fallsberg's seven steps. Results The informants' perceptions of patient safety for the women were identified in four qualitative different descriptive categories: Safeguarding the woman, Safeguarding the birth process, Respecting the individual and the team and Managing workforce and learning. Supportive care and listening to the woman were important for patient safety. It was crucial to follow labour stages and to avoid unnecessary interventions. An open and tolerant atmosphere between the healthcare professionals improved decision‐making, and a reasonable workload was essential for ensuring safe care.